Becoming Kareem : growing up on and off the court - Abdul-Jabbar, Kareem, 1947- (Little, Brown and Co., 2017)
"An autobiography about Kareem Abdul-Jabbar and his life growing up in New York, becoming the basketball star he's known to be, and getting involved in the world around him as an activist for social change"--Provided by publisher.